World on the horizon : Swahili arts across the Indian Ocean - Alpers, Edward A.; Purpura, Allyson; Meier, Prita; Fowler Museum at UCLA; National Museum of African Art (U.S.); Krannert Art Museum (Champaign, Illinois : Krannert Art Museum and Kinkead Pavilion, 2018)
The multiauthored book accompanying the World on the Horizon exhibition organized by Krannert Art Museum is the first interdisciplinary study of Swahili visual arts and their historically deep and enduring connections to eastern and central Africa, the port towns of the western Indian Ocean, Europe, and the United States. At once exhibition catalogue and scholarly inquiry, the publication features eighteen essays in a mix of formats - personal reflections, object biographies, as well as more in-depth critical treatments - and includes never before published images of works from the National Museums of Kenya and Bait Al Zubair Museum in Oman. By approaching the east African coast as a vibrant arena of global cultural convergence, these essays offer compelling new perspectives on the situated yet mobile and deeply networked social lives of Swahili objects. Moving between the broader structural relations of political economic change to more intimate narratives through which such change is experienced, the essays throw light on the ways in which the material fabric of the arts structure Swahili people's sense of self and community in an ever-changing world of oceanic and terrestrial movement. Exhibition: Krannert Art Museum, Champaign, USA (31.08.2017-24.03.2018)
Acknowledgments / Kathleen Harleman, Prita Meier and Allyson Purpura -- Guest foreword / His Excellency Ambassador Robinson Njeru Githae -- Provocations from the coast: toward a networked history of Swahili Coast Arts / Prita Meier and Allyson Purpura -- At home, at sea: onboard a dhow in the Western Indian Ocean / Nidhi Mahajan -- Through the Black Country, the sources of the Thames around the Great Shires of Lower England and down the Severn River to the Atlantic Ocean / Allan deSouza -- The Waraqa: the biography of an obligation / Fahad Bishara -- From shore to shore: people, places, and objects between the Swahili Coast and Lake Tanganyika / Stephen J. Rockel -- Thoughts on navigating Swahili horizons / Edward A. Alpers -- The Sultana in New York: a Zanaibari vessel between two worlds / Jeremy Prestholdt -- The "Colonial Moment" in the lives of objects from the Swahili Coast / Sarah Longair -- The many narratives of the Kiti cha enzi: unresolved strands of dispersal and meaning around the Indian Ocean / Nancy Um -- Reflections on the artistry and history of Swahili carved doorframes in the collection of the Lamu Museum / Athman Hussein -- Plural semiotic visions on the Swahili Coast / Janet McIntosh -- Swahili permutations: ngoma and identity in the Lamu Archipelago / Rebecca Gearhart Mafazy -- Beyond consumption: aesthetic glorious deeds and the generation of translocal society on the Swahili Coast / Paola Ivanov -- On the mimetic qualities of bowls on the medieval Swahili Coast / Jeffrey Fleisher -- Beyond the betweens: the Swahili Coast as sensed from the hinterland / Allen F. Roberts -- Cloth's many waterways: Indian Ocean textiles and the deep histories of exchange / Pedro Machado -- The art of the trade: merchant and production networks of kanga cloth in the colonial era / MacKenzie Moon Ryan -- The inscribed object: the textures and textuality of writing in Eastern Africa / Ann Biersteker -- Photography as a wish-fulfilling machine: photo studios on the East African Coast / Heike Behrend -- The Swahili world: where the horizons meet / Abdul Sheriff -- Checklist of the exhibition -- Contributor biographies
Catalog from an exhibition organized by Krannert Art Museum and Kinkead Pavilion, University of Illinois at Urbana-Champaign, held at the Krannert Art Museum and Kinkead Pavilion, University of Illinois at Urbana-Champaign, Champaign, Illinois, September 1, 2017-March 24, 2018; National Museum of African Art, Smithsonian Institution, Washington, DC, May 9-September 3, 2018; and Fowler Museum, University of California, Los Angeles, Los Angeles, California, October 21, 2018-February 10, 2019
Includes bibliographical references
Mode of access: Internet.
Keywords: Art -- Indian Ocean Region; Art -- Africa, Eastern; Art -- Africa, East